Review of amphipods of the family Pleustidae Buchholz, 1874 (Amphipoda) from the coastal waters of Sakhalin Island and Kamchatka Peninsula (Far East of Russia). IV. Subfamily Dactylopleustinae Bousfield and Hendrycks, 1994 - Labay, Vjacheslav S. (Zootaxa, 2025)
The taxonomic analysis of subfamily Dactylopleustinae Bousfield & Hendrycks, 1994 is performed. A review of subfamily Dactylopleustinae from the shelf of Northern Pacific based on all literature and own data is provided. From shallow coastal shelf waters of the Northwest Pacific are here described and figured new species of the genus Dactylopleustes Karaman & Barnard, 1979: D. awatschensis sp. nov., D. longoantennis sp. nov., D. okhotensis sp. nov., D. ornatus sp. nov., D. tzvetkovae sp. nov. Phenetic analysis of morphological relationships within the genus Dactylopleustes is performed. The key to the species of the genus Dactylopleustes is provided.